Development and validation of a diabetes mellitus treatment adherence scale. (February 2021) - Hou, Guoqiang; Fang, Ziwei; Cao, Wenjun; Shi, Yan; Xu, Xinrong; Han, Mei; Dong, Jiaxin
Abstract: Aims: The aim of this study was to develop a Diabetes Mellitus Treatment Adherence Scale (DMTAS) to fill the gap in the internationally accepted comprehensive scale. Methods: An initial item pool for the Diabetes Mellitus Treatment Adherence Scale (DMTAS) was generated based on a review of the literature and an open-ended interview. An expert group screened this initial item pool using an item-level content validity index. Then, pilot testing with 116 participants was conducted. After removing redundant and cross-loading items by exploratory factor analysis, 630 subjects were recruited to evaluate the reliability and validity of DMTAS. Analyses included internal consistency, test-retest reliability, split-half reliability, construct validity, convergent validity, and discriminant validity analysis. Results: The final DMTAS consisted of 19 items and six dimensions. The results of the exploratory factor analysis indicated that the variances of each factor explained were 23.07%, 12.28%, 9.50%, 8.25%, 7.85%, and 5.80%, and all six factors explained 66.75% of the variance in the 19 items. The items' factor loadings were all above 0.6. The results of the confirmatory factor analysis indicated that adequate fit indices (χ2 value to degrees of freedom = 3.62; root mean square error of approximation = 0.06; goodness-of-fit index = 0.92) were achieved. The Cronbach's alpha coefficient was 0.79, test–retest reliability was 0.73, and split-half reliability was 0.75. Conclusions: The DMTAS showed good validity and reliability to measure the out-of-hospital treatment adherence in patients with diabetes mellitus.